Upaya Meningkatkan Kemampuan Metodologi Mahasiswa melalui Penerapan Pendekatan - Alizar Isna (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Though lecturing (speech) method is simpler for lecturer because simple class organization and he can control entire class direction, but its weakness is he difficult to know whether students have understood his discussion or not. Studentâ€™s learning effectiveness generally limited, only a critical moment near final test. One effort to support the improvement of learning quality is applying Student Centered Learning (SCL) approach. SCL is an activity that therein student work individually and also as group to exploring problems, searching knowledge actively rather than passive knowledge receiver. Learning method based on the SCL more appropriate to be applied at learning process in university, especially at Social Research Method course (MPS). Following John W. Best, â€œthe best way to learn research is to do it,â€ so research method not only concerning cognitive domain, but also affective and psychomotor. Among learning technique based on SCL are jigsaw technique, hypothetical situation technique, and role-playing and simulation technique. .